Canada in the global village : course text - Menzies, Heather, 1949- (CEL - Canadian Publishers Collection., 1997)
This text provides an inter-disciplinary critique of the new global economy and information society, tracing its roots in the infrastructures of Canada's development from the canoes and ships of the fur trade, through the railways and telegraph of industrialization, to mass-print media, radio, television and film distribution. It draws on the works of four key thinkers-Ursula Franklin, George Grant, Harold Innis, and Marshall McLuhan-to frame contributions from Pat Armstrong, Ellen Balka, Robert Babe, Pam Colorado, James Carey, and many others.